2016
DOI: 10.1063/1.4964313
|View full text |Cite
|
Sign up to set email alerts
|

Structural and photoluminescence properties of tin oxide and tin oxide: C core–shell and alloy nanoparticles synthesised using gas phase technique

Abstract: In the present study, we report a controlled growth of tin oxide and tin oxide: carbon nanoparticles by an integrated method comprising of the gas phase agglomeration, electrical mobility based size selection, and in–flight sintering steps. The effect of in-flight sintering temperature and variation in growth environment (N2, H2 and O2) during nanoparticle formation, morphology and composition has been investigated by carrying out High Resolution Transmission Electron microscopy and X-Ray diffraction studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Figure 1(d) shows that the NPs tend to be a polycrystalline agglomerate of smaller particles with amorphous regions that could be C, or amorphous Sn oxides. Carbon is known to stabilize NPs and alloying with C has been an effective method of tuning the electronic properties of SnO x NPs 32 . Given our use of diblock co-polymer micelles for the formation of the NPs, it is likely that some carbon has been incorporated into the SnO x matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1(d) shows that the NPs tend to be a polycrystalline agglomerate of smaller particles with amorphous regions that could be C, or amorphous Sn oxides. Carbon is known to stabilize NPs and alloying with C has been an effective method of tuning the electronic properties of SnO x NPs 32 . Given our use of diblock co-polymer micelles for the formation of the NPs, it is likely that some carbon has been incorporated into the SnO x matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Second, low temperature growth of tin oxides often results in mixed phases, with SnO 2 and SnO coexisting as a result of the metastable nature of SnO 30,31 . Mixed phase alloying has been an effective method of tuning the electronic properties of SnO x NPs 32 . Finally, the surface of ITO is known to be tin-rich, with SnO 2 -like crystalline domains 3335 .…”
Section: Introductionmentioning
confidence: 99%
“…45 This type of emission which is not exactly "band gap emission" but having a lower energy than BG is known as "near band edge emission" and is already reported by several other researchers. [48][49][50][51] Mostly the visible light emission is known to be related to the defects arising from oxygen vacancies and Sn interstitials. The SnO 2 host matrix as in case of other metal oxides consists of oxygen vacancies which are created due to the escape of O 2ions from the lattice.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…It is found that the PL spectra exhibit a strong UV‐visible light emission centered at 364 nm and a blue light emission band centered at 438 nm for SnO 2 nanowire arrays, as well as a faint blue light emission centered at 436 nm for pinecone‐like SnO 2 nanoparticles, which is in agreement with the effective band gap values. However, the luminescence in SnO 2 is generally believed to originate mainly from the energy states introduced in the band gap due to defects such as tin interstitials, oxygen vacancies, or dangling bonds . The performance and properties of a material primarily depends on the efficiency and precise nature of synthesis and fabrication methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, the luminescence in SnO 2 is generally believed to originate mainly from the energy states introduced in the band gap due to defects such as tin interstitials, oxygen vacancies, or dangling bonds. 31 The performance and properties of a material primarily depends on the efficiency and precise nature of synthesis and fabrication methods. When developing a new synthesis and fabrication method for generating 1D nanostructures, the most important issue that one needs to address is the simultaneous control over dimensions, morphology, phase purity, and chemical composition.…”
Section: Introductionmentioning
confidence: 99%